Lorenzo Milani. A school committed to the poor (Journal of Parents and Teachers, 2014)
Lorenzo Milani dedicated himself to trying to remedy the problems of the poor and marginalised sectors of society; the school he organised in Barbiana was committed to human life and promoted reforms to benefit the most in need. His social, pastoral, and pedagogical proposals brought him into confrontation with the ecclesiastical hierarchy on several occasions; he also criticised the traditional school. With this, Lorenzo Milani sought to reform the unjust society in a peaceful way. He was always very dedicated and gave his life to help the poor and the disinherited.
Keywords: Lorenzo Milani; education; figures in education; Barbiana school; pedagogy